PENGARUH KONSEP DIRI, MOTIVASI, DAN DISIPLIN TERHADAP KINERJA KEPALA SEKOLAH DASAR, SE-WILAYAH KECAMATAN JAGAKARSA JAKARTA SELATAN - SRIYONO, HERU (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The objective of this research is to obtain the effects of self-concept motivation and discipline on the performance of the elementary public school-principals in Jagakarsa sub district, South Jakarta. The research was conducted by survey method with path-analysis. The sample size was 63 principals of the school. The results are as follows: (1) that the self-concept directly affects the discipline of the principals; (2) the motivation directly affects their discipline, and (3) the discipline affect directly their performance, therefore, improvement of performance of the principal should be improved by enhancing the rules and working standard.Keywords: âself-conceptâ, motivation, discipline, school-principalâs performance